Co-delivery of hydrophobic astaxanthin and hydrophilic phycocyanin by a pH-sensitive water-in-oil-in-water double emulsion-filled gellan gum hydrogel - Yu, H.; Wang, H.; Su, W.; Song, Y.; Zaky, A. A.; Abd El-Aty, A. M.; Tan, M.
Astaxanthin and phycocyanin were recommended for their bioactivities. However, limited stability and low bioavailability were not conducive to their applications in the food industry. A pH-sensitive double W1/O/W2 emulsion-filled hydrogel loaded concomitantly with astaxanthin and phycocyanin was prepared using the two-step emulsification process. First, the W1/O emulsion was fabricated using polyglycerol polyricinoleate as a hydrophobic emulsifier. Second, W1/O/W2 emulsions are typically formed by homogenizing W1/O emulsions with an aqueous phase containing sodium caseinate. Later, gellan gum was added to the double emulsion as an additional stabilizer and gelling agent to prepare the double emulsion-filled hydrogel. The influence of gellan gum on the microstructure, rheology, and stability of double emulsions was investigated. The double emulsions remained stable during 30 days' storage when the content of gellan gum was above 0.4 percent since the hydrogel formation. The microstructure of double emulsions was maintained under the acidic environment due to the network formed by gellan gum while transformed from hydrogel state to solution state since the disintegration of gellan gum network under neutral conditions. Further, based on the pH-sensitive nature of double emulsion-filled hydrogel, the co-encapsulation of phycocyanin and astaxanthin and the in vitro release behavior were demonstrated. The maximum encapsulation efficiency of phycocyanin and astaxanthin was 94.1 percent and 90.82 percent, respectively. In vitro digestion proved their intestinal targeted release ability. These results suggested that the double emulsion-filled gellan gum hydrogel can be used as a pH-sensitive carrier for intestinal targeted delivery of hydrophobic and hydrophilic food bioactive ingredients.
Keywords: PH-SENSITIVE; CONTROLLED-RELEASE; WATER-IN-OIL-IN-WATER; GELLAN GUM; ASTAXANTHIN; PHYCOCYANIN